'Performing' Fathering while Homeless: Utilising a Critical Social Work Perspective. (7th June 2017) - Roche, Steven; Barker, Justin; McArthur, Morag
Abstract: This article links sociological perspectives of fatherhood and homelessness to qualitative research with fathers experiencing homelessness. Reporting on the findings from forty in-depth interviews and two focus groups, we explore participants' conceptions of fathering and detail the material and symbolic barriers to fathering while experiencing homelessness. Fathers describe a 'performance failure' that results in 'distancing' themselves from their children, acting to conceal their inabilities to fulfil the prescriptive social norms and dominant representations of fatherhood. In response, we apply a critical social work approach to practice that concentrates on highlighting the social processes and dominant meanings of fathering and homelessness, as well as reconceptualising performances of fathering within these contexts. This is a new contribution to the literature on homelessness that expands understandings of homelessness beyond individualistic and causal explanations, as well as supports critical social work approaches to practice.